Assessment of recycling methods and processes for lithium-ion batteries - Chengetai Portia Makwarimba; Minghui Tang; Yaqi Peng; Shengyong Lu; Lingxia Zheng; Zhefei Zhao; Ai-gang Zhen (iScience, 2022)
Summary: This review discusses physical, chemical, and direct lithium-ion battery recycling methods to have an outlook on future recovery routes. Physical and chemical processes are employed to treat cathode active materials which are the greatest cost contributor in the production of lithium batteries. Direct recycling processes maintain the original chemical structure and process value of battery materials by recovering and reusing them directly. Mechanical separation is essential to liberate cathode materials that are concentrated in the finer size region. However, currently, the cathode active materials are being concentrated at a cut point that is considerably greater than the actual size found in spent batteries. Effective physical methods reduce the cost of subsequent chemical treatment and thereafter re-lithiation successfully reintroduces lithium into spent cathodes. Some of the current challenges are the difficulty in controlling impurities in recovered products and ensuring that the entire recycling process is more sustainable.